Pelatihan Pengoperasian dan Pengolahan Data Magnetometer dengan SATBINLAT PUSHIDROS TNI-AL di Teluk Jakarta - Edy Soesanto (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
This community service aims to organize training onthe operation and processing of magnetometer data in theoffshore area of Jakarta. This training is designed to providepractical knowledge and skills to the community in usingmagnetometers and processing magnetic data to supportresearch and applications in the field of offshore geology. Thepractical field session will involve operating the magnetometerin the area off the coast of Jakarta. Participants will learn abouttool operating procedures, magnetic data collection, and dataprocessing techniques to generate useful information. They willalso learn how to interpret magnetic data and analyze subsurfacegeological structures. This training aims to empower thecommunity in the use of magnetometers and magnetic dataprocessing. With the understanding and skills acquired throughthis training, participants are expected to be able to carry outmagnetic surveys in the offshore areas of Jakarta independently.This will increase understanding of the potential naturalresources and geological conditions in the area. Apart fromproviding direct benefits to the trainees, this community servicealso has the potential to make a wider contribution. Researchresults based on magnetic data collected by participants canprovide new insights about the offshore geological structure ofJakarta and the potential contained therein. This information canbe used in making decisions related to natural resourcemanagement and disaster risk mitigation in the area.